2004
DOI: 10.1016/j.bbmt.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase-1 before conditioning results in improved survival and reduced graft-versus-host disease after experimental allogeneic bone marrow transplantation

Abstract: Acute graft-versus-host disease (aGVHD) remains one of the main obstacles after allogeneic bone marrow transplantation (BMT). Using a well-established mouse BMT model in which aGVHD is induced across a haploidentical mismatch, we show that the expression of heme oxygenase-1 (HO-1) can be induced by cobalt-protoporphyrin IX (CoPP) in aGVHD target organs such as liver and bowel and that the induction of HO-1 before BMT results in improved overall survival and reduced aGVHD. Serum levels of proinflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…33 In addition, HO-1 has emerged as a major factor inducing tolerance, featuring considerable implications in the transplantation of solid organs and hematopoietic stem cells. 8,12,14,15,34,35 The tolerogenic MSCs use HO-1 to control alloactivated lymphocytes; and in line with previous observations, virtually all evaluated human MSCs 8 expressed HO-1 at various levels. Despite the evident role of HO-1 in MSC-mediated suppression, cellular levels were not associated with suppressive potency, underlining the multitude of yet not completely identified contributing factors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…33 In addition, HO-1 has emerged as a major factor inducing tolerance, featuring considerable implications in the transplantation of solid organs and hematopoietic stem cells. 8,12,14,15,34,35 The tolerogenic MSCs use HO-1 to control alloactivated lymphocytes; and in line with previous observations, virtually all evaluated human MSCs 8 expressed HO-1 at various levels. Despite the evident role of HO-1 in MSC-mediated suppression, cellular levels were not associated with suppressive potency, underlining the multitude of yet not completely identified contributing factors.…”
Section: Discussionsupporting
confidence: 61%
“…12,13 There are various preclinical transplantation models evaluating HO-1, altogether suggesting beneficial effects with regards to transplantation tolerance and tissue regeneration. 14,15 Treg induction is one of the proposed pathways how HO-1 exerts its tolerogenic effects. 11,13,15 Tregs are pivotal for the maintenance of self-tolerance and of extraordinary interest for transplantation research because of their capability of controlling autoreactive immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mRNA levels of HOX-1 were also elevated in IFN␥R Ϫ/Ϫ recipients ( Figure S1C), consistent with a response to the lung injury evident in these animals. 29,30 We were unable to detect consistent increases in chemokines known to influence IPS, including those controlled by IFN␥, [31][32][33][34] in cell lysates from lungs of allogeneic IFN␥R Ϫ/Ϫ recipients ( Figure S1D). These chemokines were also at identical levels in bronchoalveolar lavage fluid (data not shown).…”
Section: Ifn␥ Inhibits Donor Cell Migration Into the Lung And Subsequmentioning
confidence: 98%
“…HO-1 is classified as heat shock protein 32 (HSP32) and is induced in response to various stimuli such as hypoxia, endotoxins, heat shock, reactive oxygen species (ROS), or ischemia, acting as a cytoprotective protein (15). The observed inhibition of phenotypic DC maturation as a consequence of HO-1 induction (12) might be one of the major mechanisms explaining the observation that the application of CoPPIX in organ donors could lead to prolonged allogeneic graft survival in kidney (16,17), heart (18), and bone marrow transplantation (19). Additionally it has been demonstrated that treatment with CoPPIX to induce HO-1 ameliorated I/R injury (20,21) and that a single donor treatment with methylene chloride (MC) to induce CO ameliorated chronic allograft nephropathy, as reflected in the reduced number of donor-derived DCs (22).…”
Section: Inhibition Of Dendritic Cell Maturation and Function Is Indementioning
confidence: 99%